2017
DOI: 10.1016/j.celrep.2017.10.093
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Homeostatic T Cell Phenotypic Variation within the Collaborative Cross

Abstract: Summary The Collaborative Cross (CC) is a panel of reproducible recombinant inbred mouse strains with high levels of standing genetic variation, thereby affording unprecedented opportunity to perform experiments in a small animal model containing controlled genetic diversity while allowing for genetic replicates. Here, we advance the utility of this unique mouse resource for immunology research, as it allows for both examination and genetic dissection of mechanisms behind adaptive immune states in mice with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 51 publications
6
63
0
Order By: Relevance
“…The CC strains are derived from 8 founder mouse strains that include 5 classic inbred strains and 3 wild-derived strains [1][2][3][4]. We and others have previously shown that the CC can be used to model the diversity in human immune responses and reproduce human disease states not captured in standard inbred mouse models [5][6][7][8][9][10][11][12][13][14], and we additionally demonstrated that the CC better represents the large diversity in T-cell immunophenotypes represented in the human population [15]. Thus, the CC affords us with the ability to study immunity and clinical disease to infection in an animal model with diverse genotypes.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The CC strains are derived from 8 founder mouse strains that include 5 classic inbred strains and 3 wild-derived strains [1][2][3][4]. We and others have previously shown that the CC can be used to model the diversity in human immune responses and reproduce human disease states not captured in standard inbred mouse models [5][6][7][8][9][10][11][12][13][14], and we additionally demonstrated that the CC better represents the large diversity in T-cell immunophenotypes represented in the human population [15]. Thus, the CC affords us with the ability to study immunity and clinical disease to infection in an animal model with diverse genotypes.…”
mentioning
confidence: 80%
“…Spleens were prepared for flow cytometry staining as previously described [5,6,15,18]. All antibodies were tested using cells from the 8 CC founder strains to confirm that antibody clones were compatible with the CC before being used for testing.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…comm.).] Nonetheless, subsets of the available CC strains have already been used to map QTL , as evidenced by a growing list of studies (Vered et al 2014;Mosedale et al 2017;Graham et al 2017). Beyond these successes, however, it is unclear how much the reduction has affected the ability to map QTL in the CC in general.…”
Section: Introductionmentioning
confidence: 99%
“…568,569 Recognizing that an inbred strain represents an intentionally limited fraction of the spectrum of genetic variability of laboratory mice not designed or suited to model immunological endpoints at a population scale, 570,571 the CC-derived RI strains represent the genetic variability across the 7 major families of mice and offer fairly new options for dissecting genetic and molecular mechanisms of immunity and disease. 572,573 The CC is a mouse reference population with high allelic diversity constructed by a breeding strategy that systematically outcrosses 8 founder strains, followed by inbreeding to obtain new RI strains. Five of the 8 founder strains are "classical" laboratory strains including 129S1/SvImJ, A/J, C57BL/6J, NOD/ShiLtJ, and NZO/HlLtJ.…”
Section: Genetic Approachesmentioning
confidence: 99%
“…They have provided opportunities to study the evolution of complex genetic interactions. 573 The application of immunogenomics and immunonogenetics techniques on CC mice has identified QTLs, polymorphic regions, and candidate genes that control mouse immunodiversity 572 and have contributed to our understanding of susceptibilities to SARS coronavirus, West Nile virus, and Aspergillus fumigatus. [574][575][576][577] DO mice (https:// www.jax.org/strain/009376) were developed by random outcross matings of 160 CC RI lines, and the breeding strategy of continued random matings is designed to maximize their genetic diversity.…”
Section: Genetic Approachesmentioning
confidence: 99%